Lo unidimensional como disciplinario: Un diálogo entre Herbert Marcuse y Michel Foucault (2018)
The present work will seek to identify the convergent points between the idea of one-dimensionality of Herbert Marcuse as a critique of the conformation of a civilization and the analysis of the discipline carried out by Michel Foucault in the consolidation of modern normal societies. Likewise, it is also intended to point out the breakdowns of one and the other within their postulates, namely, as in the case of Marcuse, using Freud, he argues that the repression of sexuality was the expression of the instrumentalization of eros in the project of a one-dimensional civilization. However, Foucault, on the other hand and contrary to this idea, believes that beyond the repression of sexuality, this allowed the propagation of new discourses and practices that would allow exercising the power of control and normalization of individuals. The destructive sense of sexuality in Marcuse for the construction of civilization is tackled in Foucault as a space in which new disciplinary habits emerge. Thus, what for Marcuse is one-dimensional, for Foucault is disciplinary.